Controversies in neurosurgery: Irreducible basilar invagination and atlanto-axial dislocation: A trans-oral procedure may be avoided in a majority, but still may be required in some cases - P. Sarat Chandra (Indian Journal of Neurosurgery)
Basilar invagination (BI) and atlanto-axial dislocation (AAD) are mostly irreducible in nature and are quite complex pathologies to manage. Traditionally they required a trans-oral excision of odontoid process followed by a posterior instrumented fusion. This has been challenged recently, where a single staged posterior only procedure addresses both reduction and decompression in the same sitting. This evidence was based on earlier publication and also on the author’s own experience, where he described a new technique (distraction, compression, extension and reduction), which performed for the 1st time a 2-axis movement in the cranio-vertebral junction (CVJ) allowing effective reduction of both AAD and BI. This technique has now become a standard in the author’s armentorium for management of CVJ anomalies and allowed a single stage posterior only surgery for 95% of these pathologies managed by him. Although this technique could address a majority of cases of developmental BI and AAD, it becomes important to understand that a trans-oral excision of dens followed by a posterior instrumented fusion will still be required in some cases. These include certain cases of clival segmentation anomalies, very severe BI, infective pathologies like tuberculosis with circumferential compression and bony destruction and tumors. The following review article is based on the author’s personal experience of over 500 cases and discusses the advantages and limitations of single staged surgery and the indications of trans-oral surgery in this rapidly evolving field.